Produção, perda e ganho de calor em caprinos no ambiente tropical: um estudo do equilibrio térmico associado à emissão de CH4 - Fonsêca Filho, Valdir Martins da (Universidade Federal Rural do Semi-Árido, 2015)
To study the thermal balance associated to methane emission in goats in a tropical environment, it was used nine Anglo Nubian females weighing in average 53.89 kg. The animals were observed during nine consecutive days from 08:00 to 17:00. An indirect open calorimetry system was used with a facial mask adjusted on the animal s muzzle and the volume of O2, CO2, CH4 and water vapor in the inspired and expired air were determined as well as the respiratory rate, respiratory volume and the temperature of expired air. Several parameters were also collected such as rectal temperature, body surface and hair coat temperature, air temperature and humidity and black globe temperature. The results showed that when the air temperature was below 26 °C the heat exchange for long-wave radiation and convection were effective to maintain the thermal equilibrium of the animals, since respiratory rate, respiratory volume, rectal temperature and metabolic heat production parameters did not change. When the air temperature increased to 28 °C, there was a slight change in physiological responses. When air temperature was higher then 30°C the variation in the physiological parameters was significant. These results demonstrated that the thermal balance in Anglo Nubian goats protected from direct solar radiation for an air temperature between 20 and 25 °C is maintained primarily by the sensible heat loss and when these temperature reaches values higher then 30 °C can only be maintained by latent heat loss for a cost of significant changes in respiratory rate and volume, hence thermal comfort zone was varying from 20 to 27 °C. In this environment, methane emission from enteric fermentation was in average 8.41 kg year-1 animal-1. There was no significant correlation between the methane emission and with physiological and environmental parameters but with individual characteristics of each animal, such as body weight
Heat production, gain and heat loss in goats in a tropical enviroment: study of thermal balance
Keywords: Goats; Indirect calorimetry; Greenhouse - gases; Ruminants; Caprinos; Calorimetria indireta; Efeito estufa - Gases; Ruminantes; CIENCIAS AGRARIAS::MEDICINA VETERINARIA